Expanding Qualitative Research Interviewing Strategies: Zoom Video Communications - Gray, Lia M; Wong-Wylie, Gina; Rempel, Gwen R; Cook, Karen (Qualitative report, 2020)
The proliferation of new video conferencing tools offers unique data generation opportunities for qualitative researchers. While in-person interviews were the mainstay of data generation in qualitative studies, video conferencing programs, such as Zoom Video Communications Inc. (Zoom), provide researchers with a cost-effective and convenient alternative to in-person interviews. The uses and advantages of face-to-face interviewing are well documented; however, utilizing video conferencing as a method of data generation has not been well examined. The purpose of this paper is to examine the specific attributes of Zoom that contribute to high quality and in-depth qualitative interviews when in person interviewing is not feasible. While video conferencing was developed to facilitate long-distance or international communication, enhance collaborations and reduce travel costs for business these same features can be extended to qualitative research interviews. Overall, participants reported that Zoom video conferencing was a positive experience. They identified strengths of this approach such as: (1) convenience and ease of use, (2) enhanced personal interface to discuss personal topics (e.g., parenting), (3) accessibility (i.e., phone, tablet, and computer), (4) time-saving with no travel requirements to participate in the research and therefore more time available for their family. Video conferencing software economically supports research aimed at large numbers of participants and diverse and geographically dispersed populations.